Porophyllum iruyense (Asteraceae: Tageteae), a new endemic species from the north of Salta Province, Argentina - Anzuinelli, Milagros; Bartoli, Adriana (Phytotaxa, 2024)
A new species of the genus Porophyllum (Asteraceae: Tageteae), P. iruyense, is described and illustrated. Photographs of the plant in its habitat and morphological details are given. This new species is endemic to the extreme north of Salta Province, where it grows in the rocky soil of the Sierra Santa Victoria. Porophyllum iruyense is characterized by being a decumbent odoriferous gynodioecious herb, with petiolate and lanceolate to narrowly ovate leaves with marginal pellucid cavities, and dark purple corollas. This species is known by locals for its medicinal properties. A table is given to differentiate it from other species inhabiting in South America, which are also gynodioecious and have the same dark purple colour in their corollas.